652 Myocardial work in patients undergoing transcatheter aortic valve implantation: clinical value and implications for outcome. (8th December 2021) - Manzo, Rachele; Ilardi, Federica; Franzone, Anna; Angellotti, Domenico; Avvedimento, Marisa; Manzi, Lina; Verde, Nicola; Simonetti, Fiorenzo; Castiello, Domenico; Mariani, Andrea; Cirillo, Plinio; Piccolo, Raffaele; et al.
Abstract: Aims: Non-invasive myocardial work (MW) quantification has emerged in the last years as an alternative echocardiographic tool for myocardial function assessment. This new parameter provides a less loading-dependent evaluation of myocardial performance through the combined assessment of global longitudinal strain (GLS) and non-invasive left ventricle (LV) pressures. The role of MW as a marker of cardiac dysfunction and reverse remodelling in patients with severe aortic stenosis (AS) after aortic valve implantation (TAVI) has not been adequately investigated. This study aims to evaluate MW indices as early echocardiographic markers of LV reverse remodelling within a month after TAVI and their prognostic value. Methods and results: We conducted a single-centre prospective study, enrolling 70 consecutive patients (mean age 80.1 ± 5.5 years) with severe AS undergoing TAVI between 2018 and 2020, selected from the EffecTAVI registry. Exclusion criteria were prior valve surgery, severe mitral stenosis, permanent atrial fibrillation, left bundle branch block (LBBB) at baseline, and suboptimal quality of speckle-tracking image analysis. Echocardiographic assessment was performed before TAVI and at 30-day follow-up. Clinical, demographic, and resting echocardiographic data were recorded, including quantification of 2D global longitudinal strain (GLS), global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE). LV peak systolic pressure was estimated non-invasively from the sum of systolic blood pressure and trans-aortic mean gradient. One month after the procedure, there was a significant improvement of LV GLS (−17.94 ± 4.24% vs. −19.35 ± 4.31%, before and after TAVI respectively, P  = 0.002), as well as a significant reduction of GWI (2430 ± 586 mmHg% vs. 1908 ± 472 mmHg%, P  < 0.001), GCW (2828 ± 626 mmHg% vs. 2206 ± 482 mmHg%, P  < 0.001), and GWW (238 ± 207 mmHg% vs. 171 ± 118 mmHg%, P  = 0.006). Conversely, MWE did not significantly change early after intervention (90.53 ± 6.05% vs. 91.45 ± 5.05%, P  = 0.204). After TAVI, 30 patients (42.8%) developed LV dyssynchrony due to LBBB or pacemaker implantation. When the population was divided according to the presence or absence of LV dyssynchrony at 30-day follow-up, a significant reduction in GWW was found only in those without dyssynchrony (244 ± 241 vs. 141 ± 110 mmHg% with and without dyssynchrony respectively, P  = 0.002). Consistently, in this subgroup, MWE significantly improved post-TAVI (90 ± 7 vs. 93 ± 5%, P  = 0.002), while a trend of MWE reduction was observed in patients who developed dyssynchrony post-TAVI (91 ± 4 vs. 89 ± 5%, P  = 0.164). In the overall population, a baseline value of MWE< 92% was associated with an increased rate of cardiovascular events (composite of all-cause death and rehospitalization for heart failure) at 1-year follow-up (22.2 vs. 3.1%, long rank, P  = 0.016). Conclusions: In patients with severe AS undergoing TAVI a significant reduction of GWW and improvement of MWE can be detected only in those who did not develop LV dyssynchrony. In this setting, MWE lower than 92% at baseline is associated with poor outcome. Thus, MWE could represent an alternative tool for myocardial function assessment in patients receiving TAVI.